Effect of Addition of Antifungal Agents on Physical and Biological Properties of a Tissue Conditioner: An In-Vitro Study - Pragati Rawat; Swatantra Agarwal; Siddhi Tripathi (Tabriz University of Medical Sciences, 2017)
Purpose: Tissue conditioners are used for healing of abused oral tissues. They may harbour microorganisms causing oral diseases such as candidiasis compromising the health of the patient. Also, addition of antifungal agents into tissue conditioner may alter its properties. This study compares the anti-fungal property and mechanical properties of tissue conditioner containing different antifungal agents. Methods: Three antifungal agents, one synthetic - fluconazole, and two natural - oregano oil and virgin coconut oil were added into the tissue conditioner (Viscogel) in different concentrations. The antifungal property, tensile bond strength and viscoelasticity of Viscogel containing these antifungal agents were assessed after 24 hours, three days and seven days. Results: While, the highest antifungal activity was shown by Viscogel containing fluconazole, the maximum tensile bond strength was found to be of Viscogel alone (control). Although Viscogel alone and in combination of fluconazole showed deterioration in viscoelasticity, Viscogel in combination of natural agents showed no significant changes over the period of seven days. Conclusion: Incorporation of the natural agents in the tissue conditioner can be used as an effective alternative to systemic or topical synthetic antifungal agents.